Digital Transformation of Student Attendance: Backend Design Based on IoT Technology with RFID - Ari Muzakir Muzakir; Hendri (Universitas Mercu Buana Yogyakarta, 2025)
This study aims to design and implement a student attendance system based on the Internet of Things (IoT) using Radio Frequency Identification (RFID) technology at SMP Negeri 35 Palembang. The main issue addressed is the manual attendance process, which is time-consuming, error-prone, and difficult in terms of managing and accessing student attendance data. The proposed system is expected to improve efficiency and accuracy in attendance recording while providing real-time data management convenience. The methodology employed includes system design, hardware (RFID) and software (web-based application) development, and system implementation in the school environment. The research results indicate that the IoT-based attendance system successfully replaces the manual system, enhancing the speed and accuracy of attendance recording, as well as facilitating data management for the school and providing accessibility for parents. However, challenges related to user adaptation and reliance on internet connection stability still need to be addressed. As a suggestion for future research, it is recommended to develop the system with additional features such as attendance analytics and integration with the school's academic system to support data-driven decision-making